"Form follows function": the developmental morphology of the cardiac atria - Neradilova, C; Gregorovicova, M; Kovanda, J; Kvasilova, A; Melenovsky, V; Nanka, O; Sedmera, D (Physiological research, 2024)
Although the heart atria have a lesser functional importance than the ventricles, atria play an important role in the pathophysiology of heart failure and supraventricular arrhythmias, particularly atrial fibrillation. In addition, knowledge of atrial morphology recently became more relevant as cardiac electrophysiology and interventional procedures in the atria gained an increasingly significant role in the clinical management of patients with heart disease. The atrial chambers are thin-walled, and several vessels enter at the level of the atria. The left and right atrium have different structures and shape. In general, both atrial chambers have the venous part, the appendage, and the vestibule; different aspects of each part allow us to distinguish morphologically between the left and right atrium. The human atrial conduction system consists of the sinus node and the atrioventricular node with no histologically specialized conduction pathways in the atrial chamber and an interatrial connection. The data show that the propagation of the impulse depends mainly on the myocardial architecture in the atria and the orientation of the myocytes plays a significant role in conduction. To complete the picture, it is also important to know how the atria develop and what is the embryonic origin of its different structures, as this may play a role in the development of some pathological conditions such as atrial fibrillation or certain types of congenital heart defects. Functional impairment of the atria can in some situations severely compromise heart pumping function, and conversely, can support it if other areas are damaged, balancing the blood flow to the body for some time. Key words Morphology of atrial chambers, Pectinate muscles, Atrial function.
Keywords: srdeční síně; Heart Conduction System; srdce - funkce síní; Atrial Function; Animals; lidé; převodní systém srdeční; Heart Atria; Humans; zvířata